The Complex Role of STAT3 in Viral Infections - Suresh V. Kuchipudi (Journal of Immunology Research)
Signal transducer and activators of transcription-3 (STAT3) regulates diverse biological functions including cell growth, differentiation, and apoptosis. In addition, STAT3 plays a key role in regulating host immune and inflammatory responses and in the pathogenesis of many cancers. Several studies reported differential regulation of STAT3 in a range of viral infections. Interestingly, STAT3 appears to direct seemingly contradictory responses and both pro- and antiviral roles of STAT3 have been described. This review summarized the currently known functions of STAT3 in the regulation of viral replication and pathogenesis of viral infections. Some of the key unanswered questions and the gap in our current understanding of the role of STAT3 in viral pathogenesis are discussed.